All food processes have a residual risk, some are small, some very small and some are extremely small: zero risk does not exist. (June 2021) - Zwietering, Marcel H; Garre, Alberto; Wiedmann, Martin; Buchanan, Robert L
Highlights: Residual risk: risk that remains even in a fully compliant food safety system. There are several sources of residual risk and different (complementary) quantities can measure it. Residual risk becomes especially apparent for large industries or on population basis. Novel technologies (whole genome sequencing) can aid in the identification and characterization of residual risks. It is important that every actor in the system understands that zero risk is unattainable in food. Abstract : As risk-based approaches are increasingly recognized and used to manage food safety hazards, their implementation requires a recognition and appreciation of residual risk. We define residual risk as the one that remains even after a fully compliant food safety system has been implemented. As true 'zero risk' is essentially unattainable, understanding and assessing the residual risks for different products is essential for the different actors involved in the food production system. Understanding residual risk is particularly critical as improved surveillance systems (e.g. facilitated by whole genome sequencing) can detect small outbreaks and potentially link cases to a product, even when they are consequences of residual risk rather than a non-compliant food safety system. Future work on assessing residual risk for different pathogen-food combinations are essential at both the company and governmental level to further fine tune food safety systems with the definition of an acceptable residual risk.